The Page Maker Companion / PC Version 3.0 Edition - Danuloff Craig; Mcclelland Deke (Publishing Resources Inc, 1989)
Everything you need to learn and master PageMaker. Foreword: Another Book, The Publication Cycle, Installing PageMaker, Terms and Tools and Menus, A Brief Tour of PageMaker, Working in the Publication Window, Creating a Simple Newsletter, Creating and Adding Text, Editing Text in PageMaker, Using Style Sheets in PageMaker, Using Graphics in PageMaker, Creating an Intermediate Flyer, Using Color in PageMaker, Printing Publications, Creating an Advanced Catalog, Glossary, Index.